(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study proposes an enhanced ergonomic design for Nanay Aning’s Kainan, a local dining establishment located in the Tagalag Fishing Village, with the goal of improving customer experience and satisfaction. The research focuses on evaluating the restaurant’s facilities, ambiance, location, and service to identify areas that would benefit from ergonomic improvements and, in turn, enhance tourism appeal and guest comfort. A descriptive research design was employed, using a structured survey questionnaire distributed to 100 randomly selected respondents between the ages of 16 and 60. Among the respondents, 36% were aged 16–25, and 56% were male. Additionally, 49% reported a monthly income of ₱5,000 or higher, indicating their capacity and interest in spending on dining and recreational activities. The survey assessed perceptions of the restaurant’s physical and service attributes. Survey results revealed a composite mean of 2.69 for facilities, with seating comfort rated highest at 3.35. Ambiance received a mean score of 2.56, with live entertainment (3.55) and scenic surroundings (3.49) highlighted as key strengths. The location scored 2.60, pointing to concerns about accessibility and insufficient signage. Service quality emerged as a notable strength, with a mean score of 3.44, emphasizing customer appreciation for employee friendliness and efficient service. The findings suggest that enhancements in seating, flooring, restrooms, and overall accessibility are necessary to meet customer expectations. Additional improvements in visual design and decor are also recommended to elevate the dining atmosphere. These ergonomic upgrades are expected to increase customer comfort, safety, and satisfaction, while also contributing to the promotion of local tourism. The study underscores the value of ongoing ergonomic development in food service establishments to maintain competitiveness and enhance the visitor experience.